THE ROLE OF TAX ADMINISTRATION IN THE GROWTH OF THE NATIONAL ECONOMY - Babayev Farrukh Mansurovich (The Conference Hub, 2025)
The sustainable growth of any national economy depends on the effectiveness of the tax system and how well tax administration is established as a mechanism for its management. Tax administration not only provides the state budget with revenues, but also affects the overall economic dynamics by distributing resources in the economy and shaping the business environment. From this point of view, studying the theoretical foundations of tax administration is necessary for a full understanding of the processes of national economic development.